A CNTNAP1 Missense Variant Associated With Laryngeal Paralysis and Polyneuropathy in Young Great Dane Dogs - G. Diane Shelton; Missy C. Carpentier; Y. Michael Kimura; Ling T. Guo; Katie M. Minor (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Major genetic risk loci and causative mutations classified as LPN1 (Leonberger polyneuropathy type 1), LPN2 (Leonberger polyneuropathy type 2), and LPPN3 (Laryngeal paralysis polyneuropathy type 3) have been identified in Leonberger and Saint Bernard dogs with laryngeal paralysis and polyneuropathy (LPPN). Other large breed dogs, including the Great Dane, can present clinically with LPPN, and this breed previously was identified as a carrier of the LPPN3 variant. To date, homozygosity for this variant has not been identified in Great Dane dogs. Interventions Results of neurological examination, electrodiagnostic testing, and muscle and nerve biopsy samples were consistent with lower motor neuron disease associated with axonal degeneration and large nerve fiber loss in two young Great Dane dogs with gait abnormalities and respiratory difficulty. TaqMan genotyping for the three known LPPN variants confirmed a homozygous missense variant in CNTNAP1, the variant associated with LPPN3. Conclusion and Clinical Relevance A homozygous missense CNTNAP1 variant (p.G937E, XP_548083.3) has been confirmed in young Great Dane dogs that should expand the genetic testing available for LPPN in this breed and aid in the direction of breeding programs. Both dogs were euthanized because of progression of clinical signs approximately 6 months after the original diagnosis.